Analisis Pemasaran Cabai Rawit Di Desa Tutuling Jaya Kecamatan Wasile Kabupaten Halmahera Timur - Banelamo, Rolief; Pangemanan, Paulus Adrian; Waney, Nordy Fitsgerald Lucky (AGRI-SOSIOEKONOMI, 2023)
This study aims to describe marketing channels, calculate marketing margins and marketing efficiency of cayenne pepper in Tutuling Jaya Village, Wasile District. Data collection used a survey method with snowball sampling. The total sample size was 12 respondents, consisting of 4 respondents as a farmer sample, 1 collector trader sample, 2 wholesalers sample, 5 respondents as a retailer sample. The result of the research is that the marketing of cayenne pepper in Tutuling Jaya Village has 2 marketing channels. Marketing channel-1 consists of: farmers - collectors - consumers. Channel-1 marketing margin is IDR5.000/kg consisting of: marketing costs IDR3,910/kg, a profit of IDR1,090/kg. Marketing channel-2 consists of: farmers - collectors - wholesalers - retailers - consumers. The marketing margin for cayenne pepper marketing channel-2 is IDR45,000/kg, consisting of: marketing costs IDR18,965/kg, and profits of IDR26,036/kg. Marketing of cayenne pepper in Tutuling Jaya Village, Wasile District, East Halmahera Regency on marketing channel-1 was more efficient than marketing channel-2. The proportion of marketing costs to the price paid by the final consumer is relatively smaller, namely only 9.78 percent in marketing channel-1 compared to marketing channel-2 which is 23.70 percent.